An assessment of stakeholder participation on the development of Iskandar Malaysia - Rabe, Noor Suzilawati; Mohamed Osman, Mariana; Hitam, Mizan; Bachok, Syahriah (American Scientific Publishers, 2017)
This paper examines the stakeholder involvement in the development process during the establishment of Iskandar Malaysia development through qualitative and quantitative research methods. The analysis from questionnaire survey was triangulated with the interview analysis in order to provide a comprehensive overview on the process. Analyses indicated that respondents lacked the necessary awareness about the development that led to low participation in the development process of Iskandar Malaysia. Furthermore, the top-down decision making approach in Iskandar Malaysia, has led to limited involvement of the public in the overall planning of Iskandar Malaysia. Assimilation of information at all stage of development process to the public and community representatives are necessary in promoting quality and transparent decision. Good governance principal can only be achieved if the authority takes the initiative to promote bottom up approach and integrate the direct participation of the stakeholders in the formulation and planning of the region.